Can “My Body, My Choice” anti-vaxxers be pro-life? - Rulli, Tina (Bioethics, 2022)
Many “anti-vaxxers” oppose COVID-19 vaccination mandates on the grounds that they wrongfully infringe on bodily autonomy. Their view has been expressed with the slogan “My Body, My Choice,” co-opted from the pro-choice abortion rights movement. Yet, many of those same people are pro-life and support abortion restrictions that are effectively a kind of gestation mandate. Both vaccine and gestation mandates impose restrictions on bodily autonomy in order to prevent serious harms. This article evaluates the defensibility of the anti-vax pro-life position. We argue that the case for opposing gestation mandates on grounds of bodily autonomy is much stronger than the case for opposing vaccine mandates—even if fetuses have full moral status. Thus, there is a deep tension in being a pro-life, COVID anti-vaxxer concerned with bodily autonomy.